AMIR TIMUR AS A NATIONAL HERO IN UZBEK HISTORICAL PROSE - Jayrona Behzodovna Gofurova (Bright Mind Publishing, 2026)
Amir Timur (1336–1405), also known as Sahibqiron (“the possessor of fortune / justice”), is one of the central historical figures of Central Asia of the late 14th–early 15th centuries, the founder of the powerful Timurid state with its capital in Samarkand. He became famous as an outstanding military commander, statesman, and patron of science and architecture [Kadirova 2025].
Keywords: Uzbek prose, Muhammad Ali, Yevgeny Berezikov, Sarbadars, ruler.